Relationship between Selected Leadership Style and Employee Stress Level at Workplace - Choi, Mui Fong; Florianna Lendai, Michael Mulok; Helmi, Sumilan (UNIMAS Publisher, 2015)
There has been only limited research focused on the assumption of leader stress and affective well-being. Hence, this study aims to determine the relationship between leadership style and employee stress level at workplace. This study primarily took a quantitative approach for data collection and analysis. Questionnaires were distributed at three branches of banks located in Kuching, Sarawak and to their employees. The findings show that there is a relationship between autocratic leadership style and employee stress level at workplace. The strength of the relationship is weak due to r = .461, p = .002. The findings also show that democratic leadership and transformational leadership have no relationship with the employee stress level at workplace.